Acyltransferase zinc finger DHHC-type containing 2 aggravates gastric carcinoma growth by targeting Nrf2 signaling: A mechanism-based multicombination bionic nano-drug therapy - Luguang Liu; Longgang Wang; Liqing Liu; Xianlin Qu; Weizhu Zhao; Jishuang Ding; Siwei Zhao; Botao Xu; Hang Yu; Bing Liu; Jie Chai (Redox Biology, 2024)
The significant regulatory role of palmitoylation modification in cancer-related targets has been demonstrated previously. However, the biological functions of Nrf2 in stomach cancer and whether the presence of Nrf2 palmitoylation affects gastric cancer (GC) progression and its treatment have not been reported. Several public datasets were used to look into the possible link between the amount of palmitoylated Nrf2 and the progression and its outcome of GC in patients. The palmitoylated Nrf2 levels in tumoral and peritumoral tissues from GC patients were also evaluated. Both loss-of-function and gain-of-function via transgenic experiments were performed to study the effects of palmitoylated Nrf2 on carcinogenesis and the pharmacological function of 2-bromopalmitate (2-BP) on the suppression of GC progression in vitro and in vitro. We discovered that Nrf2 was palmitoylated in the cytoplasmic domain, and this lipid posttranslational modification causes Nrf2 stabilization by inhibiting ubiquitination, delaying Nrf2 destruction via the proteasome and boosting nuclear translocation. Importantly, we also identify palmitoyltransferase zinc finger DHHC-type palmitoyltransferase 2 (DHHC2) as the primary acetyltransferase required for the palmitoylated Nrf2 and indicate that the suppression of Nrf2 palmitoylation via 2-bromopalmitate (2-BP), or the knockdown of DHHC2, promotes anti-cancer immunity in vitro and in mice model-bearing xenografts. Of note, based on the antineoplastic mechanism of 2-BP, a novel anti-tumor drug delivery system ground 2-BP and oxaliplatin (OXA) dual-loading gold nanorods (GNRs) with tumor cell membrane coating biomimetic nanoparticles (CM@GNRs-BO) was established. In situ photothermal therapy is done using near-infrared (NIR) laser irradiation to help release high-temperature-triggered drugs from the CM@GNRs-BO reservoir when needed. This is done to achieve photothermal/chemical synergistic therapy. Our findings show the influence and linkage of palmitoylated Nrf2 with tumoral and peritumoral tissues in GC patients, the underlying mechanism of palmitoylated Nrf2 in GC progression, and novel possible techniques for addressing Nrf2-associated immune evasion in cancer growth. Furthermore, the bionic nanomedicine developed by us has the characteristics of dual drugs delivery, homologous tumor targeting, and photothermal and chemical synergistic therapy, and is expected to become a potential platform for cancer treatment.